Reappraisal of T1b gallbladder cancer (GBC): clinicopathologic analysis of 473 in situ and invasive GBCs and critical review of the literature highlights its rarity, and that it has a very good prognosis - BAĞCI ÇULÇİ, PELİN (My University, 2023)
There are highly conflicting data on relative frequency (2–32%), prognosis, and management of pT1b-gallbladder carcinoma (GBC), with 5-year survival ranging from > 90% in East/Chile where cholecystectomy is regarded as curative, versus 90%, similar to findings in the East. This supports the inclusion of pT1b in the \"early GBC\" category, as is typically done in high-incidence regions. Pathologic mis-staging of pT2 as pT1 is not uncommon. Cases should not be classified as pT1b unless extensive, preferably total, sampling of the gallbladder to rule out a subtle pT2 is performed. Critical appraisal of the literature reveals that the Western guidelines are based on either SEER or mis-interpretation of stage IB cases as \"pT1b.\" Although the prognosis of pT1b-GBC is very good, additional surgery (radical cholecystectomy) may be indicated, and long-term surveillance of the biliary tract is warranted.
Keywords: Tıp; Histoloji-Embriyoloji; Cerrahi Tıp Bilimleri; Patoloji; Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Sağlık Bilimleri; Temel Tıp Bilimleri; Biyokimya; Temel Bilimler; Medicine; Histology and Embryology; Surgery Medicine Sciences; Pathology; Life Sciences; Molecular Biology and Genetics; Health Sciences; Fundamental Medical Sciences; Biochemistry; Natural Sciences; Yaşam Bilimleri (LIFE); Biyoloji ve Biyokimya; PATOLOJİ; HÜCRE BİYOLOJİSİ; Life Sciences (LIFE); BIOLOGY & BIOCHEMISTRY; MOLECULAR BIOLOGY & GENETICS; PATHOLOGY; CELL BIOLOGY; Patoloji ve Adli Tıp; Moleküler Biyoloji; Hücre Biyolojisi; Pathology and Forensic Medicine; Molecular Biology; Cell Biology; Gallbladder carcinoma; Pathologic sampling; pT1b; Survival